Initial Experience Using Awake Surgery for Glioma: Oncological, Functional, and Employment Outcomes in a Consecutive Series of 25 Cases. Issue 4 (23rd January 2015) - Mandonnet, Emmanuel; De Witt Hamer, Philip; Poisson, Isabelle; Whittle, Ian; Bernat, Anne-Laure; Bresson, Damien; Madadaki, Caterina; Bouazza, Schahrazed; Ursu, Renata; Carpentier, Antoine F.; George, Bernard; Froelich, Sébastien
Abstract: BACKGROUND: Awake glioma surgery aims to maximize resection to optimize prognosis while minimizing the risk of postoperative deficits. OBJECTIVE: To evaluate oncological, functional, and employment outcomes in the first cohort of patients having this type of surgery at our institution and to determine the effects of any learning curve. METHODS: All cases of awake adult (>18 years of age) glioma surgery were recorded between the introduction of this technique in 2011 until the end of 2013. Extent of tumor resection was quantified on magnetic resonance imaging and compared with the objective prediction from a resection probability map. Cognitive status was assessed preoperatively and at 3 months postoperatively. Patients were questioned about their job and capability of working before and after surgery. RESULTS: Twenty-five patients were included in the analysis. No new motor or language deficits were noted at 6 weeks after surgery. Postoperative magnetic resonance imaging showed complete resection in 11 of 13 patients with glioblastoma and <98% resection in the other 2 patients. For patients with World Health Organization grade II glioma, 3 had total, 4 had subtotal, and 3 had partial resections. Comparison between cognitive levels before and after surgery showed no change in 4 patients, improvement in some tests in 2 patients, and deterioration in some tests in 3 patients. Of 20 patients working at the time of diagnosis, 16 returned to work. CONCLUSION: These oncological and functional results of awake glioma surgery during the learning curve are comparable to results from established centers. The use and utility of resection probability maps are well demonstrated. The return to work level is high.